A global respiratory perspective on the COVID-19 pandemic: commentary and action proposals. Issue 1 (23rd July 2020) - To, Teresa; Viegi, Giovanni; Cruz, Alvaro; Taborda-Barata, Luis; Asher, Innes; Behera, Digambar; Bennoor, Kazi; Boulet, Louis-Philippe; Bousquet, Jean; Camargos, Paulo; Conceiçao, Claudia; Gonzalez Diaz, Sandra; et al.
The novel coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1, 2]. The World Health Organization (WHO) declared the COVID-19 outbreak a pandemic on 11 March, 2020, demanding effective national and global mitigation measures, strong public health response and coordination. To date, the SARS-CoV-2 pandemic has affected over 5 million individuals worldwide with an overall 7.02% (median 3.41%, ranges 0.06% to 31.25%) case fatality ratio (European Center for Disease Prevention and Control dashboard:www.ecdc.europa.eu, as of 22 May, 2020) [3]. This ratio may be overstated since it is based primarily on hospitalised or notified cases. This paper offers practical and feasible actions to be implemented at patient, healthcare provider and community level to combat COVID-19 while attending, maintaining and strengthening ongoing health management in people with lung diseases https://bit.ly/30yNyhP